Adsorption equilibrium, kinetics and thermodynamics studies of anionic methyl orange dye adsorption using chitosan-calcium chloride gel beads. Issue 5 (30th March 2021) - Tay, S. Y.; Wong, V. L.; Lim, S. S.; Teo, I. L. R.
Abstract: Various parameters on the effectiveness of novel CS-CaCl2 beads on their removal of Methyl Orange (MO), such as the influence of CaCl2 concentrations (concentration range), contact time, adsorbent dosage, agitation speed, initial MO concentration, and temperature were investigated in batch mode. Surface characterization, adsorption properties, and the infrared spectra of CS-CaCl2 biosorbents were analyzed using various instrumental techniques.The results showed that the adsorption conditions in a descending order of 0.005 M CS-CaCl2 > 0.02 M > 0.1 M > pure CS beads at operating conditions of 200 rpm at 30 °C for 24 hours. Experimental results were in good agreement with Langmuir adsorption isotherm and pseudo second order kinetic model as both indicated by strong correlation coefficient (R 2 >0.99) confirming the chemisorption of MO on CS-CaCl2 beads. Thermodynamic studies revealed that the MO adsorption on CS-CaCl2 beads was spontaneous and exothermic with an enthalpy value of -46.573 kJ/mol at 30 °C.